Architecture Spaces to Promote Intergenerational-Friendly Environment - Vick Ter, Lim; Mohd Isa, Mohd Hafizal (MAJ - Malaysia Architectural Journal, 2020)
The age segregation society has become a physical barrier that separates the interaction between the old and young generations. Meanwhile, there are very few building typologies that combine the old and young age groups. The intergenerational interaction is complementary relationship to enhance the social development of children and older adults. The objective of this research study is to investigate the spatial requirement to support the needs of different age groups and to develop a reference to boost and enhance intergenerational-friendly environment and interaction. This research study is carried out by qualitative research by distributing the survey questionnaire to different age groups of people to analyze their interest and preference towards the intergenerational spaces and interaction activities. Precedent studies are also conducted to analyze the similar building typology and study their design strategies. Besides, an interview is conducted to understand the needs of an older adult. Throughout the study, we can understand the spatial requirement to support different age groups and the key elements to form an intergenerational space and enhance the opportunities for interaction.